UN Committee on Global Geospatial Information Management: Insediato il Comitato delle Nazioni Unite sulla gestione dell'informazione geospaziale - Salvemini, Mauro (GEOmedia, 2012)
L'iniziativa delle Nazioni Unite volta alla formazione di un comitato di esperti nella gestione della informazione geografica, già  presentata in questa rubrica in un precedente numero, ha fatto un passo avanti definitivo con l'incontro di Seoul dello scorso ottobre. The United Nations Committee of Experts on Global Geospatial Information Manage-ment, established by ECOSOC on 27 July 2011 as the official UN consultative mechanism on GGIM, has convened its inaugural meeting on 26 October 2011 in Seoul, Republic of Korea. The inaugural meeting has brought together experts from Member States and observers from international organizations to adopt the Terms of Refer-ence of the Committee, review the Rules of Procedure of the Committee, and discuss its contribution to Rio+20 Conference as well as an inventory of critical issues to be addressed by the Committee in its future sessions